Prediction of Cognitive Decline from White Matter Hyperintensity and Single-Photon Emission Computed Tomography in Alzheimer’s Disease - Tabei, Ken-ichi; Kida, Hirotaka; Hosoya, Tetsuo; Satoh, Masayuki; Tomimoto, Hidekazu (Frontiers in Neurology, 2017)
BACKGROUND: While several studies support an association of white matter hyperintensity (WMH) volume and regional cerebral blood flow (rCBF) with cognitive decline in Alzheimer's disease (AD), no reports have simultaneously considered the effects of both factors on cognitive decline. OBJECTIVE: The purpose of the present study was to compare WMH volume and rCBF in relation to cognitive function by developing a new software program to fuse magnetic resonance imaging (MRI) and single photon emission computed tomography (SPECT) data. METHOD: We used MRI, SPECT, and neuropsychological data from 182 serial outpatients treated at the memory clinic of our hospital. RESULTS: Twenty-nine AD patients fulfilled the inclusion criteria (18 female, mean age: 73.1±7.9 years, mean Mini-Mental State Examination: 23.1±3.0). Analysis of variance revealed that posterior deep WMH (DWMH) volume was significantly larger than both anterior periventricular hyperintensity (PVH) and DWMH, and posterior PVH volumes. Multivariate regression analysis showed that increased volumes of the anterior PVH and the posterior DWMH, and decreased rCBF of the parietal cortex negatively affected cognitive function. The other areas had no significant negative effects on cognitive function. CONCLUSIONS: Our findings show that the volume of the posterior WMH was significantly larger than that of other areas, and the increased posterior WMH volume and decreased rCBF of the parietal cortex negatively affected cognitive function. Therefore, the posterior WMH volume and the parietal rCBF are key parameters of cognitive decline in AD patients.